Trends, Characteristic, and Outcomes of Preterm Infants Who Received Postnatal Corticosteroid: A Cohort Study from 7 High-Income Countries - Parikh S; Reichman B; Kusuda S; Adams M; Lehtonen L; Vento M; Norman M; San Feliciano L; Isayama T; Hakansson S; Helenius K; Bassler D; et al. (KARGER, 2025)
Introduction: Our objective was to evaluate the temporal trend of systemic postnatal steroid (PNS) receipt in infants of 24-28 weeks' gestational age, identify characteristics associated with PNS receipt, and correlate PNS receipt with the incidence of bronchopulmonary dysplasia (BPD) and BPD/death from an international cohort included in the iNeo network.
Methods: We conducted a retrospective study using data from 2010 to 2018 from seven international networks participating in iNeo (Canada, Finland, Israel, Japan, Spain, Sweden, and Switzerland). Neonates of 24 and 28 weeks' gestational age who survived 7 days and who received PNS were included. We assessed temporal trend of rates of systemic PNS receipt and BPD/death.
Results: A total of 47,401 neonates were included. The mean (SD) gestational age was 26.4 (1.3) weeks and birth weight was 915 (238) g. The PNS receipt rate was 21% (12-28% across networks) and increased over the years (18% in 2010 to 26% in 2018; p < 0.01). The BPD rate was 39% (28-44% across networks) and remained unchanged over the years (35.2% in 2010 to 35.0% in 2018). Lower gestation, male sex, small for gestational age status, and presence of persistent ductus arteriosus (PDA) were associated with higher rates of PNS receipt, BPD, and BPD/death.
Conclusion: The use of PNS in extremely preterm neonates increased, but there was no correlation between increased use and the BPD rate. Research is needed to determine the optimal timing, dose, and indication for PNS use in preterm neonates.